Моделирование зонда с запирающим потенциалом в проектировании устройств телеметрии и управления - Nikolayenko, V. M.; Nikolayenko, О. V.; Venediktov, A. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The features of constructing thermo‑functional hyper‑models of plasma parameter converters are considered using the example of a probe with retarding potential. An example of building a model for a probe with two grids is given. The adaptation of the model to a form suitable for use in circuit CAD tools when designing telemetry and control devices is discussed.